Leukocyte Derived Microvesicles as Disease Progression Biomarkers in Slow Progressing Amyotrophic Lateral Sclerosis Patients - Sproviero, Daisy; La Salvia, Sabrina; Colombo, Federico; Zucca, Susanna; Pansarasa, Orietta; Diamanti, Luca; Costa, Alfredo; Lova, Luca; Giannini, Marta; Gagliardi, Stella; Lauranzano, Eliana; Matteoli, Michela; et al. (Frontiers in Neuroscience, 2019)
The lack of biomarkers in Amyotrophic Lateral Sclerosis (ALS) makes it difficult to determine the stage of the disease in patients and, therefore, it delays therapeutic trials. Microvesicles (MVs) are possible biomarkers implicated in physiological and pathological functions, however, their role in ALS remains unclear. We investigated whether plasma derived microvesicles could be overrepresented in a group of 40 patients affected by ALS compared to 28 Alzheimer’s Disease (AD) patients and 36 healthy volunteers. Leukocyte derived MVs (LMVs) compared to endothelial, platelet, erythrocyte derived MVs, were mostly present in ALS patients compared to AD patients and healthy donors. Correlation analysis corrected for the presence of confounding variables (riluzole, age at onset, site of onset, gender) was tested between PRL (Progression Rate at the Last visit) and LMVs, and a statistically significant value was found (Pearson partial correlation r=0.407, p=0.006). We also investigated SOD-1, TDP-43 intravesicular protein level in LMVs. Misfolded SOD-1 was selectively transported by LMVs and its protein level was associated with the percentage of LMVs in slow progressing patients (r=0.545, p=0.033). Our findings suggest that LMVs are upregulated in ALS patients and they can be considered possible markers of disease progression.